A Politics of Tending and Transformation. (February 2019) - Farneth, Molly
In Awaiting the King: Reforming Public Theology, James K. A. Smith gives us a liturgical political theology. The question posed here is whether that political theology attends to how the work of tending to the goods held in common by diverse democratic publics can also surprise and transform Christians and the liturgies of the Church.